Movimientos sociales : la estructura de la acción colectiva - Almeida, Paul, 1968- (CLACSO, 2020)
This book arises from an academic and political concern: the collective actions of ordinary citizens in the most diverse regions of the world could be decisive in slowing down global warming, in the fight against racism and gender violence, among many other things. forms of exploitation of society and nature. In the pages of Social Movements... a thesis appears: from the daily forms of resistance, through the creation of local movements and grassroots groups, to the waves of protest and transnational social movements, collective mobilization has created a powerful tool for human transformation, whose objectives extend to a wide range of purposes. This book focuses on the study of him from an updated and committed perspective.